Reference pricing, competition, and pharmaceutical expenditures: Theory and evidence from a natural experiment - Kurt R. Brekke; Tor Helge Holmås; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study the impact of regulation on competition between brand-names and generics and pharmaceutical expenditures using a unique policy experiment in Norway, where reference pricing (RP) replaced price cap regulation in 2003 for a sub-sample of off-patent products. First, we construct a vertical differentiation model to analyze the impact of regulation on prices and market shares of brand-names and generics. Then, we exploit a detailed panel data set at product level covering several off-patent molecules before and after the policy reform. Off-patent drugs not subject to RP serve as our control group. We find that RP significantly reduces both brand-name and generic prices, and results in significantly lower brand-name market shares. Finally, we show that RP has a strong negative effect on average molecule prices, suggesting significant cost-savings, and that patients' copayments decrease despite the extra surcharges under RP.
Keywords: I11; I18; L13; L65; 330; pharmaceuticals; regulation; generic competition; Pharmazeutisches Produkt; Staatliche Preispolitik; Preiswettbewerb; Produktdifferenzierung; Generika; Gesundheitskosten; Norwegen